Development of nanostructured starch-based materials from native sago starch (Metroxylon Sagu) - Hiang, Tay Soon (Universiti Malaysia Sarawak (UNIMAS), 2013)
Starch-based materials are promising materials in the various biomedical applications from targeted drug delivery, controlled drug release, to tissue engineering. The wide applications is due to their intriguing properties biocompatibility and biodegradability as well as their nature of being non-toxic, environmental benign, abundant and cheap. Abundant supply of hydroxyl groups on the polysaccharide chains provide ample opportunity for the modification of starch to prepare starch derivatives of various functionality. End products such as starchbased hydrogels and nanoparticles could be fabricated in order to tailor their properties for more specific fields of applications. In this research, facile methods for the synthesis of two different major products such as starch-maleate (SM) nanoparticles and starch-maleatepolyvinyl alcohol (SMP) hydrogels were being developed. The first synthetic route involved the synthesis of SMP hydrogels using native sago starch (Metroxylon sagu) as the precursor material. Starch-maleate-polyvinyl alcohol (SMP) hydrogels were prepared by reacting polyvinyl alcohol (PVA) with maleic acid (MA) substituted sago starch (SS). The substitution of MA and PVA onto the polysaccharide chain of sago starch were evidenced by the FTIR spectra which showed the presence of the carbonyl group absorption band of maleate ester, and increased intensity of the CH stretching absorption band. The surface morphology of SMP hydrogels as revealed by SEM micrograph was membrane-like with continuous matrices, and these samples were insoluble in both water and alkaline aqueous solution. TGA analysis showed that the SMP hydrogel exhibited higher thermal stability as compared to the RS, regenerated polyvinyl alcohol (RPVA) and SM samples. SMP hydrogel regenerated by freeze-drying showed substantially higher swelling ratio than hydrogel regenerated by direct precipitation under controlled conditions. The swelling behavior of SMP hydrogel could be easily controlled and modulated by varying the feeding composition of precursors or the regeneration methods. SMP hydrogel was evaluated on drug release profile studies. It showed fast release of methylene blue as a model drug within an hour, and then the rate of drug release decreased with time. The high potential utility of SMP hydrogels in biomedical applications is envisaged by its biocompatibility, low toxicity, ease of preparation and low cost. Water soluble cross-linked starch-maleate (SM) monoester gel particles from native sago starch (Metroxylon sagu) was being synthesized. SM monoester gel was initially synthesized by reacting sago starch with maleic anhydride instead of maleic acid in an aqueous medium, and followed by controlled precipitation in absolute ethanol, propan-1-ol and butan-1-ol. The substitution of maleic anhydride onto starch chains was confirmed by FTIR spectroscopy, and the degree of substitution (DS) as determined by the back-titration method was within the range of 0.03-0.21. By using different alcohol as the precipitating media, substituted SM of different compositions were obtained as indicated by the relative intensities of the carbonyl peaks in the FTIR spectra. The transformation of starch-maleate gel into cross-linked gel particles of mean diameter 445 ± 115 nm occurred upon UV irradiation in the presence of cerium(IV) ammonium nitrate as depicted in the SEM analyses. However, as revealed in TEM analyses, platelet shaped nanoparticles of average length and width 36.9 ± 7.6 nm and 17.7 ± 4.8 nm respectively were formed upon drying of the SM aqueous solution. The water absorbency and hydrophilicity of SM gel particles of DS < 0.03 was substantially lower than SM samples of DS > 0.08. In this study, SM nanoparticles were synthesized by a different approach based on the nanoprecipitation method. SM nanoparticles were obtained by adding SM solution dropwise into absolute ethanol under controlled conditions. The present study had focused mainly on modulating of the solvent and non-solvent systems in order to prepare SM nanoparticles of different morphologies. The pH of the solvent system and the nature of surfactants being added into the solvent system could influence the morphology of regenerated SM nanoparticles. SM nanoparticles of discrete and spherical shape were regenerated from both basic and acidic SM sample solution in the presence of an appropriate surfactant. SM nanoparticles with mean diameter of about 250 nm were obtained by precipitation in absolute ethanol in the presence of Brij 35 as the surfactant. Lastly, curcumin which suffers from the drawback of being extremely low water solubility and bioavailability, was loaded onto water soluble starch maleate (SM) to form curcuminloaded SM nanoparticles. The loading of curcumin onto SM was achieved by dissolving curcumin and SM separately in absolute ethanol and ethanol/aqueous (40:60 v/v) mixture respectively. Curcumin-loaded starch maleate (CurSM) were subsequently precipitated from a homogeneous mixture of these solutions in absolute ethanol based on the solvent exchange method. TEM analysis indicated that the diameter of CurSM nanoparticles ranged between 30 nm and 110 nm with a mean diameter of 50 nm. The curcumin loading capacity in CurSM nanoparticle as a function of loading duration were investigated using the UV visible spectrophotometer. The loading of curcumin onto SM increased rapidly initially with increasing loading duration and the loading capacity was reached after 12 hours. CurSM nanoparticles exhibited substantially higher water solubility than that of curcumin alone.